Fatty Liver Disease Prediction Model Based on Big Data of Electronic Physical Examination Records - Zhao, Mingqi; Song, Changjun; Luo, Tao; Huang, Tianyue; Lin, Shiming (Frontiers in Public Health, 2021)
Fatty liver disease (FLD) is a common liver disease, which poses a great threat to people's health, but there is still no optimal method that can be used on a large-scale screening. This research is based on machine learning algorithms, using electronic physical examination records in the health database as data support, to a predictive model for FLD. The model has shown good predictive ability on the test set, with its AUC reaching 0.89. Since there are a large number of electronic physical examination records in most of health database, this model might be used as a non-invasive diagnostic tool for FLD for large-scale screening.